Consensus Report on Gastroesophageal Reflux Disease in Turkey - Bor, Serhat (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Bor S. Consensus Report on Gastroesophageal Reflux Disease in Turkey. Turk J Gastroenterol 2017;28(Suppl 1); S1-S2. Full Text Turkish